PERANCANGAN KURSI UNTUK LOBY HOME STAY - Dwi Agus Susilo; Fivin Bagus Septiya Pambudi; Andreas Kabul Prasetya (SULUH: Jurnal Seni Desain Budaya, 2019)
The design of wooden home stay loby chairs is unique which is able to lift the promotion of a business. The chair design prepared for the lobby contains quality wood and has transparent fibers, so that the resulting product will be attractive. The types of wood used are Sono Keling wood and coconut wood with a water based system finishing, so that it will reduce costs..The problems in this research are 1). How to bring together a design agreement between researchers in the city of Jepara and the location of the home stay in the city of Jogjakarta. 2). Selection of raw materials for sono keling wood and coconut wood with a maximum dryness of 12%.The results obtained in this study are 1). Find the concept of chair design for the home stay lobby. 2). Able to process sono keling wood and coconut wood according to furniture production procedures. 3). Perform finishing applications with the maximum water based system material. 4). Can realize the results of special chair designs for home stay lobby rooms with various models.